Perinatal nutrition as a key regulator of genomic imprinting: a new paradigm for maternal-child health - Aronica, Lucia; Fessler, Samantha N.; Stone Rydbom, Emily; Jirtle, Randy L. (Frontiers in Nutrition, 2025)
Genomic imprinting, characterized by parent-of-origin specific gene expression, represents a critical molecular bridge between early life exposures and long-term health outcomes. Unlike most epigenetic marks, inherited gametic imprint control regions normally remain stable across tissues and throughout life, making them valuable biomarkers of early environmental influences. Recent technological advances, particularly the Human Imprintome array, have enabled comprehensive assessment of 1,488 putative imprint control regions (ICRs) that influence development, metabolism, and disease susceptibility, although ongoing experimental validation continues to refine the identification of bona fide ICRs. This perspective explores how maternal and paternal nutrition modifies offspring genomic imprinting patterns with lasting health consequences. We examine evidence from human cohort studies and experimental models demonstrating that periconceptional nutritional status affects methylation at key imprinted regions controlling growth and metabolism. Particular focus is given to one-carbon metabolism nutrients (e.g., folate, vitamin B12, choline) as critical regulators of imprinting establishment and maintenance. We propose that optimizing parental nutrition before and during pregnancy represents a powerful strategy for improving offspring health trajectories by promoting favorable imprinting patterns. The integration of imprintome analysis into maternal care offers unprecedented opportunities for personalized nutritional guidance, and early detection of epigenetic disruptions that may influence lifelong health.